2022
DOI: 10.1021/acs.iecr.2c01943
|View full text |Cite
|
Sign up to set email alerts
|

Design of Gas Separation Processes Using Type II Porous Liquids as Physical Solvents

Abstract: Solvent-based absorption systems are frequently used for industrial-scale CO2 capture from point sources. Physical and chemical solvents are well understood; however, there are drawbacks such as low gas capacity, high regeneration energy, and large operating units. Porous liquids (liquids with intrinsic microporosity) present an opportunity to improve the effectiveness of solvent-based separation processes, especially physisorption-based systems. Type II porous liquids are developed by dissolving a discrete, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…From density measurements of the PLs, the partial molar volumes of ZIF−8 were calculated, Figure 5b, and are useful as a simple comparison method. 56 The results showed that the volume contribution of ZIF−8 in solvents possessing a d W greater than 5.4 Å is similar to that of bulk ZIF−8 and decreased less than 15%, Figure S23. This further confirms that these solvents are excluded from the pores of the framework, as the volume contribution of ZIF−8 is unchanged in the PLs compared to the bulk solid.…”
Section: Pore Aperture Expansion Effects On Solvent Exclusion In Zif−...mentioning
confidence: 97%
See 3 more Smart Citations
“…From density measurements of the PLs, the partial molar volumes of ZIF−8 were calculated, Figure 5b, and are useful as a simple comparison method. 56 The results showed that the volume contribution of ZIF−8 in solvents possessing a d W greater than 5.4 Å is similar to that of bulk ZIF−8 and decreased less than 15%, Figure S23. This further confirms that these solvents are excluded from the pores of the framework, as the volume contribution of ZIF−8 is unchanged in the PLs compared to the bulk solid.…”
Section: Pore Aperture Expansion Effects On Solvent Exclusion In Zif−...mentioning
confidence: 97%
“…Partial molar volume: Partial molar volumes of formed PLs were calculated following previously reported methods. 56 In general, the measured density (g/mL) of the formed dispersions was plotted as a function of the ZIF concentration (g/mL). The data was fitted linearly with a fixed slope, and the slope and y-intercept of the fitted line were used to calculate the partial molar volume of the ZIFs.…”
Section: Density Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…20 Additionally, the CC13 POC was a component of one of the first reported PLs in 2015 6 and has been subsequently used in preparation of Type 2 PLs. 21 Altering the POC in the PLs has resulted in size and shape selectivity for gas capture along with substantial increase in gas adsorption capacity. 7,22,23 For example, a Type 2 PL formed from an imine-based POC and a 15-crown-5 ether had an 8-fold increase in CH 4 adsorption over the neat liquid, 6 while the use of scrambled POCs in Type 2 PL doubled the amount of CH 4 adsorbed per POC.…”
Section: Introductionmentioning
confidence: 99%